Digital and smart technologies in agriculture in Germany: Identification of key recommendations for sustainability actions - Frauke Geppert; Tsvetelina Krachunova; Sonoko Dorothea Bellingrath-Kimura (Expertenkommission Forschung und Innovation (EFI), 2024)
In this study, we identified currently available digital and smart technologies for German agriculture and classified their applicability. We differentiated our findings by three categories and ten sub-categories, including complex systems for data collection, software- and hardware-based technologies with a total of 201 commercial technologies. Additionally, we took an inventory of the country-specific agricultural environmental impacts and conducted an online survey on the barriers and potentials of digital technologies in relation to sustainability, followed by an experts' dialogue with stakeholders from agriculture, policy, industry, research, and civil societies, and a literature review assessment. On this basis, we elaborated key recommendations for further actions that prevail barriers and promote potentials for a sustainable digitalisation in German agriculture. We also provided best-practice examples from other European countries. Our findings showed that policy actions are urgently needed to establish a broader use of digital and smart technologies for sustainability purposes in daily farm work.
Keywords: 330